The Phonology of Tailue Tribe in Dontan Village, Xienghone District, Sayyaboury Province : https://doi.org/10.69692/SUJMRD080219 - NIMNUAN, Laion; SYVONGSAK, Somthapheuy; DOUNGCHANH, Boy; SONETHALA , Amphai; INVANKHAM, Maiphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This study focused on the phonetic system of Tailue tribe in Donton village, Xienghon District, Saiyabouly Province by applying the qualitative research through the interview, reading, observation, analysis, and classification of its system. The objective of this study was to examine the phonetic system of consonants, vowels, and tone marks of local Tailue tribe according to the list of vocabulary from Li (1977) which included 1107 Tai words and the list of phonetic tone marks of local Tai from Gedney (1959). The result of this study was that, there are 20 of beginning consonants as /k/, /kh/, /N/, /c/, /s/, /ø/, /d/, /t/, /th/, /n/, /b/, /p/, /ph/, /f/, /m/, /j/, /l/, /w/, /?/, /h/, 2 mix consonants as /kw/, /khw/ and 8 of ending consonants as /-p/, /-t /, /-k /, /-m /, /-n /, /-N/, /-w /, /-j /. There are 18 of root vowels as /a/, /aù/, /i/, /iù/, /µ/, /µù/, /u/, /uù/, /e/, /eù/, /E/, /Eù/, /o/, /où/, /«/, /«ù/, //, /ù/. Based on this research, any of the mixed vowels were not found. For the tone mark, 6 types of it were found - low-up (25) sounds, middle-up (34) sounds, middle (33) sounds, low-up (23) sounds, middle-down (32) sounds, low-up (24) sounds.